2019
DOI: 10.1152/japplphysiol.00115.2019
|View full text |Cite
|
Sign up to set email alerts
|

Heat therapy improves soleus muscle force in a model of ischemia-induced muscle damage

Abstract: Leg muscle ischemia in patients with peripheral artery disease (PAD) leads to alterations in skeletal muscle morphology and reduced leg strength. We tested the hypothesis that exposure to heat therapy (HT) would improve skeletal muscle function in a mouse model of ischemia-induced muscle damage. Male 42-wk-old C57Bl/6 mice underwent ligation of the femoral artery and were randomly assigned to receive HT (immersion in a water bath at 37°C, 39°C, or 41°C for 30 min) or a control intervention for 3 wk. At the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…This seems unlikely given the accumulating evidence derived from animal studies that repeated heat stress enhances muscle strength and prevents disuse-induced muscle weakness. For instance, we recently reported that repeated immersion in a water bath at 37°C and 39°C for 3 weeks enhanced maximal absolute force of the soleus muscle in a model of ischemia-induced muscle damage (23). Similarly, Yoshihara and colleagues reported that 3 days of whole-body HT using a heat chamber (40-41°C for min) abrogated ventilator-induced diaphragm contractile dysfunction in rats (40).…”
Section: Limitationsmentioning
confidence: 92%
“…This seems unlikely given the accumulating evidence derived from animal studies that repeated heat stress enhances muscle strength and prevents disuse-induced muscle weakness. For instance, we recently reported that repeated immersion in a water bath at 37°C and 39°C for 3 weeks enhanced maximal absolute force of the soleus muscle in a model of ischemia-induced muscle damage (23). Similarly, Yoshihara and colleagues reported that 3 days of whole-body HT using a heat chamber (40-41°C for min) abrogated ventilator-induced diaphragm contractile dysfunction in rats (40).…”
Section: Limitationsmentioning
confidence: 92%
“…Chronic heat therapies have been used in both animal models of PAD and patients with PAD. Roseguini's group has explored the impacts of chronic heat therapy in murine models of chronic hindlimb ischemia [47,48]. Kim et al (2019) found that muscular mass (+7%) in the ischemic limb was greater following heat therapy compared to control [47].…”
Section: Clinical Applications Of Heat Therapymentioning
confidence: 99%
“…Roseguini's group has explored the impacts of chronic heat therapy in murine models of chronic hindlimb ischemia [47,48]. Kim et al (2019) found that muscular mass (+7%) in the ischemic limb was greater following heat therapy compared to control [47]. In a similar investigation, Kim et al (2020) found that in addition to preserving muscle mass, heat therapy treatment may also be beneficial for improving body composition in an obese murine model of hindlimb ischemia.…”
Section: Clinical Applications Of Heat Therapymentioning
confidence: 99%
“…Considering the aspects of limited conduit artery blood flow and impaired endothelium-dependent vasodilation during physical activity in this population, there will probably be an increased reliance on the microcirculation to meet the metabolic demands of the contracting muscle. Therefore, novel strategies targeting skeletal muscle myopathy to reverse muscle atrophy [66,67] that can be used in addition to those targeting capillary rarefaction [68,69] hold great potential to produce greater and more sustainable clinical impact.…”
Section: Skeletal Muscle Pathology In Padmentioning
confidence: 99%